STAT5A/B Gene Locus Undergoes Amplification during Human Prostate Cancer Progression - Haddad, Bassem R. (American Society for Investigative Pathology, 2013)
The molecular mechanisms underlying progression of prostate cancer (PCa) to castrate-resistant (CR) and metastatic disease are poorly understood. Our previous mechanistic work shows that inhibition of transcription factor Stat5 by multiple alternative methods induces extensive rapid apoptotic death of Stat5-positive PCa cells in vitro and inhibits PCa xenograft tumor growth in nude mice. Furthermore, STAT5A/B induces invasive behavior of PCa cells in vitro and in vivo, suggesting involvement of STAT5A/B in PCa progression. Nuclear STAT5A/B protein levels are increased in high-grade PCas, CR PCas, and distant metastases, and high nuclear STAT5A/B expression predicts early disease recurrence and PCa-specific death in clinical PCas. Based on these findings, STAT5A/B represents a therapeutic target protein for advanced PCa. The mechanisms underlying increased Stat5 protein levels in PCa are unclear. Herein, we demonstrate amplification at the STAT5A/B gene locus in a significant fraction of clinical PCa specimens. STAT5A/B gene amplification was more frequently found in PCas of high histologic grades and in CR distant metastases. Quantitative in situ analysis revealed that STAT5A/B gene amplification was associated with increased STAT5A/B protein expression in PCa. Functional studies showed that increased STAT5A/B copy numbers conferred growth advantage in PCa cells in vitro and as xenograft tumors in vivo. The work presented herein provides the first evidence of somatic STAT5A/B gene amplification in clinical PCas.